Comparing the efficacy of live vs. video instructional demonstrations in dental education: a systematic review and meta-analysis - Rawan N. AlKahtani; Banna M. Alnufaiy; Refal S. Albaijan; Sarah M. Alnafaiy; Farah M. Elfakhri; Suha M. Aljudaibi (BMC Medical Education)
Abstract Background This systematic review and meta-analysis were conducted to investigate the effects of live and video demonstrations of various dental procedures on undergraduate students’ performance and satisfaction scores. Materials and methods A comprehensive search was conducted across multiple databases, including MEDLINE (OVID), PubMed, Scopus, and Web of Science, supplemented by a manual search of bibliographic references from retrieved articles. The aim was to identify relevant randomized controlled trials and quasi-experimental trials that compared live demonstrations to video demonstrations in dental education, specifically focusing on undergraduate students’ performance and satisfaction scores assessed using practical assessment rubrics and satisfaction questionnaires. The quality of included studies was assessed using the modified Downs and Black quality assessment tool. Results A total of 3686 studies were identified, of which 2222 studies remained following duplicate removal. Based on title and abstract screening 2188 studies were excluded and full text of 34 studies were comprehensively appraised for eligibility. This resulted in the inclusion of 10 studies in the systematic review, nine of which were classified as good, while one study was considered as fair. Of these, 8 studies were included in the meta-analysis.Students’ feedback reveals distinct preferences, with video demonstrations being commended for repeatability and clarity, while live demonstrations were valued for real-time interaction and guidance. Meta-analysis revealed that video-based learning significantly enhanced educational outcomes across various measures, including knowledge acquisition and practical skills over live demonstrations. Conclusion Video demonstrations emerge as viable alternatives to live demonstrations in dental education for teaching clinical procedures. Video demonstrations offer distinct benefits, including accessibility and repeatability, while live demonstrations provide essential interactive opportunities that contribute significantly to the learning experience in dental education.